2021
DOI: 10.1002/eji.202048984
|View full text |Cite
|
Sign up to set email alerts
|

Insights into coronavirus immunity taught by the murine coronavirus

Abstract: Coronaviruses (CoVs) represent enveloped, ss RNA viruses with the ability to infect a range of vertebrates causing mainly lung, CNS, enteric, and hepatic disease. While the infection with human CoV is commonly associated with mild respiratory symptoms, the emergence of SARS-CoV, MERS-CoV, and SARS-CoV-2 highlights the potential for CoVs to cause severe respiratory and systemic disease. The devastating global health burden caused by SARS-CoV-2 has spawned countless studies seeking clinical correlates of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Laboratory MHV strains have been broadly studied to identify harmful coronavirus factors and elucidate host mechanisms of antiviral pathogenicity (see, [ 65 , 66 , 67 , 68 ] and references therein). The major MHV viruses used are MHV-3, MHV-A59, MHV-JHM, and MHV-S.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory MHV strains have been broadly studied to identify harmful coronavirus factors and elucidate host mechanisms of antiviral pathogenicity (see, [ 65 , 66 , 67 , 68 ] and references therein). The major MHV viruses used are MHV-3, MHV-A59, MHV-JHM, and MHV-S.…”
Section: Discussionmentioning
confidence: 99%
“…The infection with the human CoV is commonly associated with mild respiratory symptoms. However, the emergence of beta subgroup CoV strains, including SARS-CoV-1, MERS-CoV, and SARS-CoV-2, highlights the potential of CoV to cause severe respiratory and systemic disease (Van Der Hoek et al, 2004;Sariol and Perlman, 2020;Grabherr et al, 2021). SARS-CoV-1-infected individuals were first reported in 2002 with approximately 8100 reported cases (Peng et al, 2003;Zhao et al, 2003;Sariol and Perlman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it has been shown that MHV shares inhibitory effects for virus entry with SARS-CoV-2 [ 34 ]. Furthermore, MHV is closely related to pro-inflammatory response, similar to SARS-CoV-2, including induction of cytokines such as TNF and IL-1β, and IFN-gamma [ 35 ]. Additionally, MHV and SARS-CoV-2 have typical decay patterns in an environment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%